Functionalization of medium-chain-length poly(3-hydroxyalkanoates) as amphiphilic material by graft copolymerization with glycerol 1,3-diglycerolate diacrylate and its mechanism - Ansari, Nor Faezah; Annuar, Mohamad Suffian Mohamad (Taylor & Francis, 2018)
Glycerol 1,3-diglycerolate diacrylate (GDD) was graft copolymerized onto poly(3-hydroxyoctanoate-co-3-hydroxyhexanoate) P(3HO-co-3HHX) to render the latter more hydrophilic. Grafting of P(3HO-co-3HHX) backbone was performed using benzoyl peroxide as free radical initiator in homogenous acetone solution. The graft copolymer of P(3HO-co-3HHX)-g-GDD was characterized using spectroscopic and thermal methods. The presence of GDD monomer in the grafted P(3HO-co-3HHX) materials linked through covalent bond was indicated by spectroscopic analyses. Different parameters affecting the graft yield viz. monomer concentration, initiator concentration, temperature and reaction time were also investigated. Water uptake measurement showed that P(3HO-co-3HHX)-g-GDD copolymer became more hydrophilic as the GDD concentration in the copolymer increased. Introduction of hydroxyl groups via grafted GDD monomers improved the wettability and imparted amphiphilicity to the graft copolymer, thus potentially improving their facility for cellular interaction. Thermal stability of grafted copolymer reduced with increased grafting yield. The activation energy, Ea, for the graft copolymerization was calculated at ∼ 51 kJ mol−1. Mechanism of grafting reaction was also proposed.